Sister chromatid exchange frequency in B-cells stimulated by TPA in chronic lymphocytic leukemia - (:unkn) unknown (ELSEVIER SCIENCE INC, 2000)
Chronic lymphocytic leukemia (CLL) is characterised by the clonal proliferation and accumulation of neoplastic B-lymphocytes. The median age of the patients is 65 years, and more men than women are affected. The overwhelming majority of CLLs are of B-cell origin. Chromosomal aberrations have been detected in more than 50% of the B-cells obtained from peripheral blood samples after appropriate stimulation with polyclonal B-cell mitogens. The analysis of sister chromatid exchange is a cytogenetic technique used to show DNA damage due to an exchange of DNA fragments between sister chromatids. In this study, lymphocytes from 22 patients with CLL-B (7 female, 15 male; mean age 64.09 +/- 7.56 years) were stimulated by a B-cell mitogen (TPA) and BrdU added at the 24 h of the culture. Metaphase chromosomes were stained with a fluorescence plus Giemsa technique after a standard harvest procedure. The frequency of sister chromatid exchange was found to be increased significantly P = .02) in patients with CLL-B (8.24 +/- 1.36 per metaphase) compared to controls (7.25 +/- 1.42 per metaphase). We conclude that the increased frequency of sister chromatid exchange in chronic lymphocytic leukemia after stimulation with a B-cell mitogen (TPA) may reflect DNA instability and defective DNA repair in these patients. (C) 2000 Elsevier Science Inc. All rights reserved.
Keywords: DNA-DAMAGE